Bronchiolitis obliterans syndrome due to donor‐specific HLA‐antibodies. Issue 3 (23rd July 2015) - Kauke, T.; Kneidinger, N.; Martin, B.; Dick, A.; Schneider, C.; Schramm, R.; Meimarakis, G.; Preissler, G.; Eickelberg, O.; von Dossow, V.; Behr, J.; Hatz, R.; et al.
Abstract Chronic lung allograft dysfunction (CLAD) is a limiting factor for long‐term survival in lung transplant recipients. Donor‐specific human leukocyte antigen (HLA)‐antibodies (DSA) have been suggested as potential risk factors for CLAD. However, their impact on clinical outcome following lung transplantation remains controversial. We performed a single‐center study of 120 lung transplant recipients transplanted between 2006 and 2011. Patient sera were investigated before and after transplantation. The sera were screened by means of Luminex® technology (Luminex Inc., Austin, TX, USA) for IgG‐HLA‐class I and class II antibodies (ab). Using single antigen beads, DSA were identified and correlated retrospectively with clinical parameters. After transplantation 39 out of 120 patients (32.5%) were positive for HLA‐ab. The incidence of de novo DSA formation was 27 of 120 patients (22.5%). Eleven of 27 (41%) of de novo DSA‐positive patients developed BOS compared to 13 of 93 (14%) DSA‐negative patients (p = 0.002). Furthermore, the generation of de novo DSA was independently associated with the development of BOS in multivariable analysis [hazard ration (HR) 2.5, 95% confidence interval (CI) 1.0–6.08; p = 0.046). Our results indicate that de novo DSA are associated with the development of BOS after lung transplantation. Monitoring of HLA‐ab after transplantation is useful for identifying high‐risk patients and offers an opportunity for early therapeutic intervention.